First distributional record of ant species (Hymenoptera: Formicidae) from Botanical Garden, Puducherry, India - K, Gowri; K, Sankaraiyah (Journal of Applied Entomologist, 2024)
The current study examines the ant distribution at the Botanical Garden in the Union Territory of Puducherry, India, as there are still no prior ant diversity reports from this site. Ant community is an essential unit of any ecosystem because they serve as ecosystem engineers. But the field of myrmecology has received very little attention in India. During the investigation, 12 ant species from four subfamilies were identified, including Myrmicinae, Ponerinae, Formicinae, and Pseudomyrmicinae. This work is the first report on the distribution of ant species from this location.